Postdivorce Counselling and Dispute Resolution: Services, Ethics, and Competencies - Chang, Jeff (Canadian Journal of Counselling and Psychotherapy, 2016)
This article orients practitioners to postdivorce counselling, assessment, and dispute resolution services. First, 11 services that mental health practitioners can provide to individuals and families following separation and divorce are described. I then discuss ethical issues that can arise with divorcing and postdivorce families. Finally, I describe how Canadian counsellor education programs provide a sound base for work with divorcing families and articulate the additional knowledge, skills, and attitudes necessary for specialized practice. Canadian counsellors, practicing with ethical awareness and prudence, can do important work to alleviate the suffering of divorcing families.